Review articleRadiation-induced brachial plexus neuropathy – aetiopathogenesis, risk factors, differential diagnostics, symptoms and treatment - Gosk, Jerzy; Rutowski, Roman; Reichert, Paweł; Rabczyński, Jerzy (Folia Neuropathologica, 2007)
The success of radiation oncology has led to longer patient survival. This provides a greater opportunity for radiation injuries of the peripheral nerves to develop. Brachial plexus neuropathy in cancer patients may result from either tumour recurrence or as a consequence of radiation therapy. Distinguishing between radiation injury and cancer disease recurrence as a cause of brachial plexus dysfunction may be difficult. In this article the most important principles of the differential diagnostics have been presented. Furthermore the aetiopathogenesis of brachial plexus neuropathy after radiotherapy has been discussed as well as main risk factors, symptoms of plexopathy and methods of treatment. It ought to be emphasized that complications of radiation therapy sometimes occur many years after treatment and this may create difficulties in initial diagnostics